Estratégias e desafios no ensino e aprendizagem de matemática no contexto do ensino remoto emergencial - DOURADO, Moisés Rêgo (2022)
The health crisis caused by the COVID-19 pandemic in Brazil and the world has brought critical challenges for humanity. Regarding Basic Education, it was no different, as the teaching and learning process underwent unprecedented and significant transformations, thus emerging natural needs for students and teachers to know, analyze, describe and study methodological actions during the period of implementation of Emergency Remote Education. In this way, concepts and methodologies about remote education are discussed to support and qualify the pedagogical practices adopted to develop non-face-to-face activities. For this purpose, we used bibliographic and documentary research in books, scientific articles, official documents, technical notes, and data obtained from the lesson plans and reports prepared by the teacher who developed the remote activities. Finally, the data analyzed are the result of pedagogical practices adopted in Mathematics classes of the 9th grade (last year of middle school in Brazil). The results reveal that remote teaching is a real challenge for the current pedagogical practice, demanding new teaching methodologies in which the use of digital information and communication technology is essential, modeling the role of the teacher and the student, and resignifying the concepts and practices of teaching and learning. In conclusion, the present work demonstrates that new paths lead to the permanence of remote teaching and its methodologies, even with the return of face-to-face classes.